2002
DOI: 10.1002/1521-4095(20020503)14:9<658::aid-adma658>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Color-Tunable Colloidal Crystals from Soft Hydrogel Nanoparticles

Abstract: The tunability of the lattice spacing of hydrogel colloidal crystals has been achieved by simply varying the water content of the microgel pellet before annealing and crystallization. The manipulation of the lattice constant of the crystals and therefore of the wavelength of the resultant Bragg peak, i.e., the color of the crystal, leads to a myriad of photonic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
198
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(203 citation statements)
references
References 1 publication
3
198
0
2
Order By: Relevance
“…In a similar system using N,N ′ -methylene bis(acrylamide) to crosslink the particles, the initial color could be locked in, stabilizing the thermoresponsive behavior over multiple cycles. [ 68 ] Watanabe's group has investigated a range of different opaline hydrogels that respond to changes in temperature and, in certain cases, to specifi c ions. They demonstrated that interconnected sphere arrays exhibited reversible changes in the position of refl ection peaks with temperature, whereas spheres embedded in a hydrogel matrix merely changed peak intensity as the temperature was varied.…”
Section: Temperaturementioning
confidence: 99%
“…In a similar system using N,N ′ -methylene bis(acrylamide) to crosslink the particles, the initial color could be locked in, stabilizing the thermoresponsive behavior over multiple cycles. [ 68 ] Watanabe's group has investigated a range of different opaline hydrogels that respond to changes in temperature and, in certain cases, to specifi c ions. They demonstrated that interconnected sphere arrays exhibited reversible changes in the position of refl ection peaks with temperature, whereas spheres embedded in a hydrogel matrix merely changed peak intensity as the temperature was varied.…”
Section: Temperaturementioning
confidence: 99%
“…The dramatic response and stimuli-specific behavior makes these materials extremely valuable for numerous applications, [1][2][3][4][5] including drug delivery, [6][7][8][9][10][11] chemical separations, [12,13] sensors, [14][15][16] catalysis, [17] enzyme immobilization, [18] and color-tunable crystals. [19] Several potential applications of these microgels, such as 'smart' actuators, on-off switches, and pulse-release, require a short response time. Currently, numerous strategies are employed to speed up the response kinetics of typical thermo-responsive hydrogel microspheres such as poly(N-isopropylacrylamide) (PNIPAM) microgels.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Research work on the further application of structure color has also been carried out. [7][8][9][10][11][12][13] For example, Xia [9a] developed a photonics paper/ ink system by embedding 3D colloidal crystals with liquids capable of swelling the elastomer, and the system could serve as a reusable recording medium where no pigments would be required for color display. From a practical point of view there are two main drawbacks that restrict the application of colloidal crystal films.…”
Section: Introductionmentioning
confidence: 99%